Continued Detention Involvement and Adolescent Marijuana Use Trajectories. (January 2014) - Ewing, Sarah W. Feldstein; Schmiege, Sarah J.; Bryan, Angela D.
Justice-involved youth have high rates of marijuana use. Less is known about what may drive these rates, particularly when justice-involved youth return to the community. One factor that has been implicated is continued detention involvement. Yet, it is unknown how this factor may influence marijuana use trajectories. Using longitudinal growth curve modeling, the researchers evaluated the association between continued detention involvement and marijuana use trajectories in two large, ethnically diverse samples of community-based, justice-involved youth. Across both samples, marijuana use decreased over time for youth with continued detention involvement but did not change for youth without continued detention involvement. These findings underscore the importance of attending to the influence of detention involvement in community-based, justice-involved adolescents' marijuana use trajectories. This study also highlights the importance of coordinating prevention/intervention programming for justice-involved youth once they are in the community.